Persepsi Guru dalam Pembelajaran Berbicara dengan Metode Online di SMP - Marpaung, Ivan Christian; Kamil, Acep Bahrum; Wahyuna, Yuna Tresna (Peneliti.net, 2024)
This research explores teachers’ perception in learning speaking toward onlne method in junior high school in Bekasi. This research used qualitative approach with case study method with purposive sampling. The site and participant of this research was three teachers from junior high school in Bekasi. Observation and interview as the instruments of this research. Findings of this research was (1) The student do not have a mobile phone, (2) Bad internet connection, (3) Student’s laziness during online learning, (4) The Importance of face-to-face in learning speaking skills. Considering the findings and responses from teachers’ the teachers’ perception in learning speaking toward online method in junior high school in Bekasi was lacking facilities and infrastructure in online learning for students, such as not having a cellphone, internet quota, etc. The bad internet connection that students often experience. Students become lazy about learning, especially when learning speaking Skills. For example, not responding when online learning takes place, not being disciplined when participating in online learning, being late in sending assignments, etc. English teachers have difficulty in measuring students’ understanding and abilities during online learning, especially speaking Skills.